Mothers' experiences after single-event multilevel orthopedic surgery in cerebral palsy: A descriptive qualitative study - Gulsah Kose; Arzu Aydogan; Sevinc Tastan; Cemil Yildiz (Tehran University of Medical Sciences, 2020)
Background & Aim: Mothers with children with cerebral palsy experience various problems during the care process, especially after surgery. Since these problems of parents directly affect the care provided to the child, it is essential to evaluate the problems that families experience in this process. This study aims to explore the experiences of mothers of children with cerebral palsy and to find out how these mothers care for their children that underwent single-event multilevel orthopedic surgery due to cerebral palsy. Methods & Materials: A descriptive phenomenological study was used to explore the life experiences of 24 participants who had children with CP. This study was performed in the Department of Orthopedics at a Training and Research Hospital in Turkey, between March and July 2015. The study was completed with the participation of 24 mothers who had children with cerebral palsy. A qualitative, face-to-face and in-depth interview technique were used for data collection. Colaizzi's method and Professional Software for Qualitative and Mixed Methods Research 11 software were used for analysis. Results: The mean age was 37.29±6.86. Based on the mothers' care experiences data, three main themes were identified, namely "Be concern about the process," "Facing the Difficulties and Coping," "Adaptations the changing family lifestyle." Conclusion: The findings demonstrated that CP affects intra-family relations and functions, and contributes to various physical and mental health problems, and financial statement. We believe that the findings may help healthcare professionals to provide and plan education in the field of healthcare services in a way that helps families cope with the process successfully.